"I'd rather injure somebody else than get injured": An introduction to the study of exposure to physical violence among young people experiencing homelessness. (20th April 2020) - Heerde, Jessica A.; Pallotta-Chiarolli, Maria
ABSTRACT: Homeless young people are at risk for a range of negative health and behavioral outcomes, and they commonly report exposure to physical violence, as both perpetrators and victims. Semi-structured interviews focusing on exposure to physical violence were conducted with 18 homeless young people in Victoria, Australia. Results showed perpetration of physical violence occurred as a form of self-protection. Painful experiences of physical victimization were also described. Injuries were sustained as a result of both physical violence perpetration and victimization. Results suggest an important duality exists between homeless young people's acceptance of exposure to physical violence as normal and requiring emotional detachment at the time of its occurrence, and later reflection about exposure to physical violence with emotional engagement and problematizing the necessity of normalization and detachment. Shame, stigma, and unequal power relationships were described in relation to interactions with health professionals. Future research exploring violence as a response to vulnerability and subsequent feelings of shame and stigma in homeless young people is especially warranted.